Linking What We Eat to Our Mood: A Review of Diet, Dietary Antioxidants, and Depression - Qingyi Huang; Huan Liu; Katsuhiko Suzuki; Sihui Ma; Chunhong Liu (MDPI AG, 2019)
Studies have shown that diet and nutrition play significant roles in the prevention of depression and its clinical treatment. The present review aims to provide a clear understanding of the associations between diet patterns, specific foods, nutrients such as antioxidants, and depression. As a result, balanced dietary patterns such as the Mediterranean diet and certain foods such as fish, fresh vegetables, and fruits have been associated with a lower risk of depression or depressive symptoms, while high-fat Western diets and sugar-sweetened beverages have been associated with higher risk of depression or depressive symptoms. Dietary antioxidants such as green tea polyphenols or isoflavonoid intake have been negatively associated with depression or depressive symptoms. It is concluded that diet patterns, specific foods, and antioxidants play important roles in the prevention and clinical treatment of depression.